2015
DOI: 10.1080/19420862.2015.1046664
|View full text |Cite
|
Sign up to set email alerts
|

Development of a stable low-dose aglycosylated antibody formulation to minimize protein loss during intravenous administration

Abstract: The physical and chemical integrity of a biopharmaceutical must be maintained not only during long-term storage but also during administration. Specifically for the intravenous (i.v.) delivery of a protein drug, loss of stability can occur when the protein formulation is compounded with i.v. bag diluents, thus modifying the original composition of the drug product. Here we present the challenges associated with the delivery of a low-dose, highly potent monoclonal antibody (mAb) via the i.v. route. Through para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Colleagues reported that MMF Cellcept ® 1-10 mg/mL in 5% dextrose injection PVC bags stored at 4 ± 1 or 25 ± 2°C remained stable for the entire study period, set at 7 days (Certain et al, 2002 Regarding the evaluation of MMF sorption levels during the preparation steps of infusion bags using Equashield ® CSTD sets, the low values obtained in our work were considered negligible according to the acceptable drug sorption limit (10%) recommended by pharmacopeias (Jin, You, Jeon, Byon, & Hwang, 2017;Morar-Mitrica et al, 2015). Although previous studies have examined the impact of this interaction (adsorption) between different drugs and the plastic infusion bags (Beitz et al, 1999;Benaji et al, 1994;Blum, 1982;Dine et al, 1992;Moorhatch & Chiou, 1974), none has included MMF and a CSTD system.…”
Section: Discussionmentioning
confidence: 68%
“…Colleagues reported that MMF Cellcept ® 1-10 mg/mL in 5% dextrose injection PVC bags stored at 4 ± 1 or 25 ± 2°C remained stable for the entire study period, set at 7 days (Certain et al, 2002 Regarding the evaluation of MMF sorption levels during the preparation steps of infusion bags using Equashield ® CSTD sets, the low values obtained in our work were considered negligible according to the acceptable drug sorption limit (10%) recommended by pharmacopeias (Jin, You, Jeon, Byon, & Hwang, 2017;Morar-Mitrica et al, 2015). Although previous studies have examined the impact of this interaction (adsorption) between different drugs and the plastic infusion bags (Beitz et al, 1999;Benaji et al, 1994;Blum, 1982;Dine et al, 1992;Moorhatch & Chiou, 1974), none has included MMF and a CSTD system.…”
Section: Discussionmentioning
confidence: 68%
“…High concentration mAb solutions are regularly diluted in saline for IV dosing. ( 17 , 18 ) Not only is the diluent composition a factor for aggregation, but we have also found that the dilution itself is also very important. We have found that bevacizumab, ranibizumab and aflibercept are very prone to diminished function once removed from their manufacturer’s vial and diluted.…”
Section: Introductionmentioning
confidence: 63%
“…Only recently has attention turned to the investigation of antibody stability of low-dose antibodies as well as clinical dilutions of mAb medications. ( 17 ) We became interested in the stability of dilute mAb solutions when we were developing and validating methods for mAb in vitro transscleral permeation using traditional two-compartment Franz permeation cells.…”
Section: Introductionmentioning
confidence: 99%
“…Auto-oxidation of several existing polyoxy ethylene groups in Tweens at high temperatures is considered as the major adverse effect of these additives, which could conclusively facilitate protein unfolding and aggregation up on accelerated storage conditions or induced protein fragments [ 12 ]. Since Cysteine has exhibited antioxidant activity in formulations of different peptides and proteins [ 30 , 31 ], the improved synergistic effect between Cysteine and Tween 20 would be likely due to inhibition of Tween 20 auto-oxidation and the subsequent stabilization of the antibody. Generated peroxidase in polysorbates could cause degradation of proteins.…”
Section: Resultsmentioning
confidence: 99%